Study on In Situ Stress Measurement and Surrounding Rock Control Technology in Deep Mine. (8th September 2020) - Qin, Zhongcheng; Cao, Bin; Liu, Yongle; Li, Tan
Abstract : In situ stress is the direct cause of roadway deformation and failure in the process of deep mining activities. The measured data of in situ stress in the Shuanghe coal mine show that the maximum principal stress is 44.94~50.61 MPa, and the maximum principal stress direction is near horizontal direction, which belongs to tectonic stress field. The maximum horizontal principal stress is 1.66~1.86 of the vertical stress. The horizontal principal stress controls the deep stress field. According to the measured data of in situ stress, the high-strength prestress bolt and cable collaborative support form is designed in the Shuanghe coal mine. Based on the stress field research of bolt and cable, the optimal prestress ratio of bolt and cable is proposed as 3. When the prestress ratio of bolt and cable is constant, the smaller the length ratio of bolt and cable is, the better the effect of prestressed field formed by cooperative support is. The results are applied to the support design of the mining roadway in the Shuanghe coal mine. Through the field monitoring test results, it is found that the maximum roof subsidence is 86 mm, the maximum floor deformation is 52 mm, and the maximum deformation of two sides is 125 mm. The surrounding rock control effect of the roadway is good, and the surrounding rock deformation conforms to the engineering technology standard requirements. The research results of this paper can provide some reference for the surrounding rock support of high ground stress mining roadway under similar conditions.